Insulin infusion sets associated with adverse events: strategies for improved diabetes education - Neves, Ana Lucia Domingues; Martins, Luiz Eduardo Galvão; Gabbay, Mônica Andrade Lima; Pascali, Paula; de Oliveira, Tiago; Martinazzo, Aldo; Dib, Sérgio Atala; Casarini, Dulce Elena; Aredes, Sebastião Vagner; Tenorio, Fernanda Silva; Cunha, Tatiana Sousa (Frontiers in Medicine, 2023)
Introduction: Insulin Infusion Sets (IIS) play a crucial role in ensuring the safe delivery of insulin through a Continuous Subcutaneous Insulin Infusion (CSII) for individuals with Type 1 Diabetes (T1D). Advancements in therapy have highlighted the need to address issues such as unexplained hyperglycemia and IIS occlusion. Objective: To investigate the adverse events (AEs) associated with IIS that impact the treatment of T1D, with a specific focus on promoting effective educational practices. Methods: 118 patients under treatment at the Ambulatory Insulin Pump of the Federal University of São Paulo Diabetes Center responded to a semi-structured questionnaire. Over six months, a nurse researcher interviewed them via video calls. Results: Catheter-related adverse events (AEs) included catheter knots, catheter folding, and catheters' accidental traction. Cannula's AEs were mainly related to cannula fixation adhesive, insulin leakage, bleeding episodes, and skin problems. The cannula patch tends to detach easily in hot conditions or when used for more than three days, leading to local itching. Adhesive glue can cause redness and pain. Insulin leakage typically occurs after the catheter disconnects from the cannula, the cannula's accidental traction, or beneath the cannula patch. Bleeding has been reported inside the cannula or at the insertion site, resulting in local pain and, in some cases, obstruction of insulin flow. When cannulas' accidental traction occurs, it is recommended to replace the entire IIS system. In situations involving bleeding, leakage, insulin odor, or unsuccessful attempts to correct hyperglycemia with a "bolus" of insulin, it is advisable to change the IIS and evaluate appropriate techniques for handling and infusing the device. Besides, regular inspections of the device and reservoir are essential. Conclusion: Serious AEs can occur even in cases where the occlusion alarm is not activated, leading to interruptions in insulin flow. Conversely, in less severe situations, alarm activation can occur even in the absence of insulin flow interruption. Catheters' accidental traction and catheters' bent are commonly encountered in everyday situations, while issues related to the cannula directly affect blood glucose levels. AEs related to the cannula often involve insulin leakage into the skin, bleeding, and skin events attributed to its adhesive.